Pedicled Groin Flap for Coverage of Soft Tissue Defect of Hand - Parajuli, Nirajan Prasad; Yadav, Krishna Kant; Sah, Rajeev Kumar; Bohra, Lalit Kumar; Sundas, Milan (Medical Journal of Eastern Nepal, 2023)
Background: Distant pedicle flaps like groin flaps are still considered workhorse flaps for the coverage of soft tissue defects of the hand. In the era of free flaps pedicle flaps are still considered as primary flaps by many surgeons. Pedicle flaps are easy to raise, require less experience and microsurgical facility. Methods: In this retrospective descriptive study, patients in whom groin flap was done for reconstruction of hand soft tissue defects were included from April 2017 to April 2022. Results: Thirty-three flaps were included in this study with an average patients’ age of 34.6 years. There were 24 males and 9 females. All flaps survived and served the purpose of covering wounds. Complications like finger and shoulder stiffness were seen in 18 (54.5%), partial necrosis was seen in 4 (12.1%), marginal necrosis in 2 (6%), and infection was seen in 5 (15.2%) patients. Donor sites were healthy after insetting of the flap and did not show any sign of morbidities like infection or bad scarring. Conclusion: Groin flaps are versatile flaps. Where microvascular free flaps are not possible due to severity of injury or due to unavailability of the facility for microvascular free flap groin flap is an excellent option. With less complication, those flaps can be executed easily.